MEMBANGUN MINAT BACA ANAK USIA DINI DENGAN MENGGUNAKAN BUKU BERCERITA BERGAMBAR - Nurkhasyanah, Alfiyanti; Asriani, Asriani; Apriloka, Dinita Vita; Triani, Lili (LPPM Universitas Bina Bangsa, 2024)
This study aims to explore how the use of picture story books can build reading interest in early childhood. A qualitative approach with descriptive methods was used in this study, involving observation, in-depth interviews, and documentation studies. The subjects of the study were children aged 3-6 years in several Kindergartens (TK), as well as their teachers and parents. The results of the study showed that picture story books were effective in increasing children's reading interest. Children who regularly interact with picture books showed a significant increase in reading interest, story comprehension, and active engagement during reading activities. Illustrations in books help children understand and remember stories better, as well as encourage their creativity and imagination. The use of picture books also contributes to the development of children's language skills, with increased vocabulary and confidence in speaking. Active support from parents and teachers has been shown to be important in fostering children's reading interest. Children who receive this support show stronger reading habits. The findings also show that children have a preference for books with bright colors, interesting characters, and adventurous stories